Evidence for gravity wave drag in the boundary layer of a numerical forecast model: a comparison with observations. (7th October 2016) - Lapworth, A.; Osborne, S. R.
Abstract : The main effect of gravity wave drag is generally considered to be an increased drag on upper tropospheric flow. However, the nocturnal boundary layer overland is often extremely stable and in this case there can be considerable gravity wave drag on near‐surface flow, affecting turbulent fluxes and screen temperatures. In order to determine whether this type of drag is correctly represented in numerical forecast models, a dataset of winds and temperatures output from a forecast model is compared with an archive of observations from two surface sites. Comparison with the output from a one‐dimensional model is used to differentiate gravity wave drag from form drag and flow blocking. The results indicate that a gravity wave drag component is probably present in the stable boundary‐layer flows of the forecast models. However the strength of the drag is not as great as that observed. This results in larger model turbulent fluxes and increased surface temperatures from those measured overnight.